2020
DOI: 10.21203/rs.3.rs-24972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circ_0084927 promotes cervical carcinogenesis by sponging miR-1179 that suppresses CDK2, a cell cycle-related gene

Abstract: Background: Cervical cancer (CC) is a highly malignant tumor. Evolving researches on CC have unveiled a concept that circRNA exerts important roles in CC progression. In this study, we mainly explored the role of a novel circRNA, circ_0084927, and its regulatory network in the development of CC.Methods: qRT-PCR was applied to evaluate the expression of circ_0084927, miR-1179 and CDK2 mRNA in CC tissues and cells. Dual-luciferase reporting experiments and RNA immunoprecipitation (RIP) assay were conducted to va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the expression levels of CDK2, CDK4 and CDK6 are often upregulated in various types of cancer, and are associated with tumorigenesis by interacting with other proteins (22,23). For example, Qu et al (24) reported that CDK2 served a key role in circular RNA (circ)_0084927/microRNA (miR)-1179 signaling axis-mediated cervical cancer development. Zhao et al (25) found that CDK6 knockdown suppressed gastric cancer cell proliferation via regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the expression levels of CDK2, CDK4 and CDK6 are often upregulated in various types of cancer, and are associated with tumorigenesis by interacting with other proteins (22,23). For example, Qu et al (24) reported that CDK2 served a key role in circular RNA (circ)_0084927/microRNA (miR)-1179 signaling axis-mediated cervical cancer development. Zhao et al (25) found that CDK6 knockdown suppressed gastric cancer cell proliferation via regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In CC, numerous circRNAs have been considered to be oncogenic drivers [15]. For instance, circ_0084927 regulated the development of CC via miR-1179/CDK2 axis [16], and circ_0000745 promoted CC cell proliferation and inhibits cell apoptosis by miR-409-3p/ATF1 axis [17]. In this study, compared with the relative normal tissues and cells, circ_0002762 was up-regulated in human CC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 83%
“…Other studies have shown up-regulation of a number of CDK2-interactiong circRNAs such as hsa_circ_0000520 [128], circ_0084927 [129] and circZFR [130] in cervical cancer patients. Notably, up-regulation of circZFR has been associated with lymphatic metastasis in this type of cancer [130].…”
Section: Investigations In Clinical Samplesmentioning
confidence: 92%